Detail to pay attention to when translating Malay to Chinese - Hoe, Foo Terng; Tan, Teow Ghee; Lam, Kai Chee (Kajang: New Era University College, 2021)
When Malay students do translation exercises, the common mistake is students translate the sentences directly, a result of their mother tongue negative transfer. The grammatical structure of Malay language is different from that of Chinese language. If Malay sentences are literally translated into Chinese, readers may find the sentences difficult to comprehend, Due to the mother tongue interference, Malay students will unconsciously employ the Malay grammar when doing translation exercises. The translated Chinese sentence will make the readers find them weird to read. There are quite a few things to be aware of when doing translation so that these translated sentences would not pose much problem if the translation procedure is strictly followed. When translating Malay words or a phrases into Chinese, most of the word and phrase structures remain unchanged and can be translated directly, such as verb and nouns, noun and verbs, vecb and adjectives, adjective and verbs, adjective and adjectives, as well as verb and verbs. Only in the phrase structure of noun and nouns, noun and adjectives, and verb and adverbs, the position of words and word in phrases should be interchanged (left ~ right interchange). In addition, the word ‘的(de)’, “得(de)’, “是(shi)’, “了 (le)’ must be added after the translation if necessary, After translating ‘this(ini)’ & ‘that(itu)’, quantifiers also must be added. “在(at)’ and ‘去(g0)/来(come)’ need to be considered and inserted too in the sentence. Subject must be put at the beginning of the interrogative sentence. Uncertain words should be put behind the subject. These are the aspects that have to be paid attention in the translation exercise,